2021
DOI: 10.4103/atm.atm_283_20
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diagnostic assessment programs on the diagnosis and treatment of patients with lung cancer in Ontario, Canada

Abstract: INTRODUCTION: Diagnostic assessment programs (DAPs) were implemented in Ontario, Canada, to improve the efficiency of the lung cancer care continuum. We compared the efficiency and effectiveness of care provided to patients in DAPs relative to usual care (non-DAPs). METHODS: Lung cancer patients diagnosed between 2014 and 2016 were identified from the Ontario Cancer Registry. Using administrative databases, we identified various health-care encounters 6 months before di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
(17 reference statements)
4
18
0
1
Order By: Relevance
“…Patients with esophageal cancer waited 1 week longer than patients with lung cancer in Ontario to receive a PET/CT scan and have a consultation with a radiation or medical oncologist, which may have translated into a longer time until treatment (median of 46 vs 40 days). 14 The reasons for these differences are unknown, despite treatment at the same designated thoracic surgery centers. However, there is limited evidence that longer wait times are associated with worse survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with esophageal cancer waited 1 week longer than patients with lung cancer in Ontario to receive a PET/CT scan and have a consultation with a radiation or medical oncologist, which may have translated into a longer time until treatment (median of 46 vs 40 days). 14 The reasons for these differences are unknown, despite treatment at the same designated thoracic surgery centers. However, there is limited evidence that longer wait times are associated with worse survival.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 The association of having a longer time until treatment with better overall survival has been demonstrated previously in patients with cancer and is likely due to a triaging effect. 14 , 20 Patients with more overt symptoms are more likely to have advanced disease and be diagnosed or treated urgently, which may only be partially accounted for by stage and is likely to confound any associations between wait times and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies describing barriers to early cancer diagnosis services focused on barriers to accessing existing programs. For instance, a recent systematic review described barriers to accessing lung cancer diagnosis programs [ 23 ]. The studies in this review showed that poor relationships between primary care providers and patients, lack of accessibility of services for patients due to geography, and patient and provider lack of awareness of cancer symptoms and treatments were barriers to access.…”
Section: Discussionmentioning
confidence: 99%